Active base isolation of buildings subjected to seismic excitations. - Chang, Chia-Ming (Earthquake engineering & structural dynamics.)
Structural control technology has been widely accepted as an effective means for the protection of structures against seismic hazards. Passive base isolation is one of the structural control techniques to enhance the performance of structures subjected to severe earthquake excitations. Isolation bearings employed at the base of a structure naturally increases its flexibility, but concurrently results in large base displacements. The combination of base isolation with active control, i.e. active base isolation, creates the possibility of achieving a balanced level of control performance in reductions of either floor accelerations or base displacements. Many theoretical papers have been written by researchers regarding active base isolation. A few experiments have been performed to verify these theories; however, challenges in appropriately scaling the structural system and modeling the complex nature of control?structure interaction (CSI) have limited the applicability of these results. This paper presents the development and experimental verification of an active base isolation system for a seismically excited building. First, the general problem formulation and control design procedure are provided. Subsequently, the experimental setup is described; unique features include low-friction pendular bearings and custom-manufactured low-force hydraulic actuators. A new system identification procedure that can effectively capture the phenomena of CSI is then presented and used to realize control-oriented models of the system. H 2/LQG control strategies employing different performance objectives are developed and experimentally evaluated on a six degree-of-freedom shake table in the Smart Structures Technology Laboratory at the University of Illinois at Urbana-Champaign. The proposed control strategies are shown to perform effectively for a wide range of seismic excitations.